2017
DOI: 10.1063/1.4994712
|View full text |Cite
|
Sign up to set email alerts
|

Ultrafast and nonlinear spectroscopy of brilliant green-based nanoGUMBOS with enhanced near-infrared emission

Abstract: The synthesis, characterization, ultrafast dynamics, and nonlinear spectroscopy of 30 nm nanospheres of brilliant green-bis(pentafluoroethylsulfonyl)imide ([BG][BETI]) in water are reported. These thermally stable nanoparticles are derived from a group of uniform materials based on organic salts (nanoGUMBOS) that exhibit enhanced near-infrared emission compared with the molecular dye in water. The examination of ultrafast transient absorption spectroscopy results reveals that the overall excited-state relaxati… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
13
0

Year Published

2020
2020
2021
2021

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 11 publications
(15 citation statements)
references
References 58 publications
2
13
0
Order By: Relevance
“…As shown in Figure 6c, experimental data are fit with a global analysis technique using a sum of exponential functions. 17,18,55 The equation used i n t h e g l o b a l a n a l y s i s fi t is of the form…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…As shown in Figure 6c, experimental data are fit with a global analysis technique using a sum of exponential functions. 17,18,55 The equation used i n t h e g l o b a l a n a l y s i s fi t is of the form…”
Section: Resultsmentioning
confidence: 99%
“…We have previously investigated the ultrafast excited-state dynamics of different types of nanoGUMBOS using transient absorption spectroscopy. , In one study, we reported observation of tunable intermolecular energy transfer in crystalline ruthenium bipyridine-–bis­(pentafluoroethylsulfonyl)­imide ([Ru­(bipy) 3 ]­[BETI] 2 ) nanoGUMBOS in colloidal suspension in water . Size-dependent relaxation dynamics were observed in these nanoGUMBOS, characterized by decay dynamics similar to the Ru­(bipy) 3 Cl 2 dye with an added relaxation pathway from intermolecular energy transfer .…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…T.E. Karam et al [127] . introduced thermally stable, brilliant green‐based nanoGUMBOS [BG][BETI] (BG=brilliant green) (Figure 17).…”
Section: Synthesis and Applications Of Nanogumbosmentioning
confidence: 99%
“…T.E. Karam et al [127] introduced thermally stable, brilliant green-based nanoGUMBOS [BG][BETI] (BG = brilliant green) ( Figure 17 MIPs (molecularly imprinted polymers) exhibited property of molecular separation and sensing while inferring of electrostatic/hydrogen bonding under aqueous medium has become a major problem. To overcome this drawback of conventional MIPs, S. Hamdan et al [128] introduced four NGMIPs (nano-GUMBOS molecular imprinted polymers) that applied in the enantiorecognition for chiral amino acids (D-and L-tryptophane) ( Table 3, Entry 15-18).…”
mentioning
confidence: 99%